2012
DOI: 10.1016/j.ultsonch.2012.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ultrasound on growth, bioconversion of isoflavones and probiotic properties of parent and subsequent passages of Lactobacillus fermentum BT 8633 in biotin-supplemented soymilk

Abstract: This study aimed to evaluate the effects of ultrasound on Lactobacillus fermentum BT 8633 in parent and subsequent passages based on their growth and isoflavone bioconversion activities in biotin-supplemented soymilk. The treated cells were also assessed for impact of ultrasound on probiotic properties. The growth of ultrasonicated parent cells increased (P<0.05) by 3.23-9.14% compared to that of the control during fermentation in biotin-soymilk. This was also associated with enhanced intracellular and extrace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 49 publications
2
7
0
Order By: Relevance
“…The novelty of such work was that, since lactic acid bacteria often present poor survival in, for instance, yoghurt (due to low pH and low acid tolerance), yeast can utilize the organic acids produced during fermentation thereby increasing the pH of the environment and, hence, the viability Finally, several treatments have been studied in an attempt to optimize the bioactivation of soy isoflavones. For instance, Ewe et al [50] evaluated the effects of ultrasounds on Lactobacillus fermentum BT8633 growth and isoflavone bioconversion activity in soymilk, finding out that the growth of ultrasonicated cells increased by 3.2-9.1%, compared to the control. This increased growth was associated with enhanced intracellular and extracellular (8.4-17.0% and 16.7-49.2%, respectively) β-glucosidase activity, leading to increased bioconversion of isoflavones glycosides to aglycones, possibly due to the reversible permeabilized membrane of ultrasonicated cells that facilitated the transport of molecules across the membrane.…”
Section: Bioactivation Of Isoflavones In Soymilkmentioning
confidence: 99%
“…The novelty of such work was that, since lactic acid bacteria often present poor survival in, for instance, yoghurt (due to low pH and low acid tolerance), yeast can utilize the organic acids produced during fermentation thereby increasing the pH of the environment and, hence, the viability Finally, several treatments have been studied in an attempt to optimize the bioactivation of soy isoflavones. For instance, Ewe et al [50] evaluated the effects of ultrasounds on Lactobacillus fermentum BT8633 growth and isoflavone bioconversion activity in soymilk, finding out that the growth of ultrasonicated cells increased by 3.2-9.1%, compared to the control. This increased growth was associated with enhanced intracellular and extracellular (8.4-17.0% and 16.7-49.2%, respectively) β-glucosidase activity, leading to increased bioconversion of isoflavones glycosides to aglycones, possibly due to the reversible permeabilized membrane of ultrasonicated cells that facilitated the transport of molecules across the membrane.…”
Section: Bioactivation Of Isoflavones In Soymilkmentioning
confidence: 99%
“…The low frequency ultrasound can improve the permeability of cells by forming transient pores on the cell membrane. These pores increase the transfer of substances across the membrane and the secretion of metabolites like intracellular enzymes and subsequently stimulate cellular growth and proliferation (Ewe, Wan‐Abdullah, Alias, & Liong, ; Huang et al, ; Mota et al, ; Yeo & Liong, ). Dai et al () investigated the effect of sonication on the growth of Saccharomyces cerevisiae and its membrane permeability.…”
Section: Resultsmentioning
confidence: 99%
“…Afterward, the absorbance was read at 560 nm (Wang et al, 2006). , & Liong, 2012;Huang et al, 2017;Mota et al, 2018;Yeo & Liong, 2013). Dai et al (2017) investigated the effect of sonication on the growth of Saccharomyces cerevisiae and its membrane permeability.…”
Section: Scavenging Activity Of Superoxide Anion Radicalmentioning
confidence: 99%
“…Ewe Wan‐Abdullah Bhat et al (2012) demonstrated that ultrasound frequency of 30 kHz and 100‐W power at different amplitudes (20%, 60%, and 100% amplitude) for 2–3 min) facilitated the growth of lactobacilli in milk with viable counts exceeding 9 log cfu/ml and also enhanced β‐glucosidase activity of the cells which enabled isoflavone glucosides bioconversion to bioactive aglycones in soymilk. In another study by Ewe Wan‐Abdullah Alias et al (2012), there was an increase in the growth of ultrasonicated L. fermentum BT 8,633 in biotin supplemented soymilk by 3.23%–9.4% when compared to the control with an enhanced intracellular and extracellular bioconversion of isoflavones glucosides to aglycones during fermentation under ultrasonic conditions of 30‐kHz frequency and 100‐W power for 2 min. In the stimulation of low‐intensity ultrasound on skim milk fermentation by Huang et al.…”
Section: Ultrasound In Fermentation Technologymentioning
confidence: 95%